FIH Regulates Cellular Metabolism through Hydroxylation of the Deubiquitinase OTUB1. - Carsten C Scholz; Javier Rodriguez; Christina Pickel; Stephen Burr; Jacqueline-Alba Fabrizio; Karen A Nolan; Patrick Spielmann; Miguel A S Cavadas; Bianca Crifo; Doug N Halligan; James A Nathan; Daniel J Peet; et al. (PLoS Biology)
The asparagine hydroxylase, factor inhibiting HIF (FIH), confers oxygen-dependence upon the hypoxia-inducible factor (HIF), a master regulator of the cellular adaptive response to hypoxia. Studies investigating whether asparagine hydroxylation is a general regulatory oxygen-dependent modification have identified multiple non-HIF targets for FIH. However, the functional consequences of this outside of the HIF pathway remain unclear. Here, we demonstrate that the deubiquitinase ovarian tumor domain containing ubiquitin aldehyde binding protein 1 (OTUB1) is a substrate for hydroxylation by FIH on N22. Mutation of N22 leads to a profound change in the interaction of OTUB1 with proteins important in cellular metabolism. Furthermore, in cultured cells, overexpression of N22A mutant OTUB1 impairs cellular metabolic processes when compared to wild type. Based on these data, we hypothesize that OTUB1 is a target for functional hydroxylation by FIH. Additionally, we propose that our results provide new insight into the regulation of cellular energy metabolism during hypoxic stress and the potential for targeting hydroxylases for therapeutic benefit.